2003
DOI: 10.1046/j.1365-2141.2003.04213.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD38 and CD20 expression as assessed by quantitative flow cytometry in chronic lymphocytic leukaemia

Abstract: Summary. CD38 expression on chronic lymphocytic leukaemia (CLL) cells is a poor prognostic factor, however, methods for measuring this vary. The QuantiBRITE TM flow cytometry (FC) system yields an absolute antigen expression value (antibodies bound/cell, ABC) and may be useful in standardizing CD38 expression analysis. We evaluated cryopreserved pretreatment CLL cells for CD20 ABC, CD38 ABC, and percentage of CD38 + B cells from 131 patients requiring therapy. The 92 patients (70%) with ‡ 100 CD38 ABC had wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
(75 reference statements)
2
21
0
Order By: Relevance
“…Quantitative Flow cytometry (QFCM) is being investigated as a diagnostic tool in the clinical laboratory and as a prognostic indicator in patients receiving antibodybased therapy (21)(22)(23)). In the current study, CD22 expression was quantitated by measuring the mean number of fluorescently-labeled antibodies bound per cell, or ABC, utilizing the QuantiBRITE assay and a custom conjugated anti-CD22 antibody with 1:1 PE to antibody ratio (F/P ratio 1:1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative Flow cytometry (QFCM) is being investigated as a diagnostic tool in the clinical laboratory and as a prognostic indicator in patients receiving antibodybased therapy (21)(22)(23)). In the current study, CD22 expression was quantitated by measuring the mean number of fluorescently-labeled antibodies bound per cell, or ABC, utilizing the QuantiBRITE assay and a custom conjugated anti-CD22 antibody with 1:1 PE to antibody ratio (F/P ratio 1:1).…”
Section: Discussionmentioning
confidence: 99%
“…The complete antibody panels, including antibody combinations used, were chosen based on the number of cells and previous histological diagnosis and immunophenotypic data. Erythrocytes were lysed by incubating with lysing solution (150 mM NH 4 Cl, 10 mM KHCO 3 , 0.1 mM EDTA) for 10 min at room temperature (maintained at [21][22][23] C) at a ratio of 1:9 (volume of sample: volume of lysing solution). Specimens were then washed with phosphate buffered saline (PBS) to remove cytophilic antibodies before determining cell number.…”
Section: Specimen Processingmentioning
confidence: 99%
“…A significant shorter time to first treatment and a shorter disease-specific survival was seen in patients with more than 250 ABC as compared to those with less than 250 ABC. Hsi et al (9) showed a significant shorter OS for patients with CD38 ABC >100, when compared to a group with <100 CD38 ABC. However, the complex patterns of CD38 expression by B-CLL cells in some patients prompted Ghia et al (10) to propose an approach in which they divided patients into three groups according to CD38 expression by the leukemic cells: those who were uniformly CD38 negative, those who were CD38 positive, and those with a bimodal profile (i.e., 2 distinct populations, CD38 negative and positive).…”
mentioning
confidence: 99%
“…Tam et al (6) showed that CLL patients with trisomy 12 showed strong expression of CD20 and had a high rate of response to rituximab-based therapy. However, Hsi et al (7) reported that CD20 expression was not significantly correlated with clinical factors, and CD20 expression was also not associated with overall survival (OS). The prognostic significance of CD20 expression in B-cell precursor acute lymphoblastic leukemia has been extensively studied in children and adults.…”
mentioning
confidence: 99%